KATA KERJA BANTU MODAL DALAM NOVEL THE STARS SHINE DOWN KARYA SIDNEY SHELDON - Giban, Marthinus; Pamantung, Rina P.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTS     This study is an attempt to describe, identify, classify, and analyze modal verbs in the novel The Stars Shine Down by Sidney Sheldon. Modal is a verb that combines with another verb to indicate modal or tense. A modal expresses necessity, ability, permission, possibility, necessary, willingness, and others.The problem of this study is to find out the forms and meanings of modals in the novel The Stars Shine Down by Sidney Sheldon. The method which used in this study is descriptive method.The data of modals are collected from the sentences found in the novel. The theory which used is taken from Beaumont and Granger. The result shows that there are seven forms of method found in the novel, namely can, could, may, should, will, and would.The meanings of modals are: can, ability, permission, possibility, and offering. Could expresses possibility, ability, disabilty. Will expresses request. Would expresses polite request. Must expresses obligation, and might expresses necessity.Key Wordal : Modal Verbs, Novel: The Stars Shine Down, Grammatical Analysis.